14-3-3 protein inhibits CaMKK1 by blocking the kinase active site with its last two C-terminal helices - Petrvalska, Olivia; Honzejkova, Karolina; Koupilova, Nicola; Herman, Petr; Obsilova, Veronika; Obsil, Tomas (Protein science, 2023)
Ca2+ /CaM-dependent protein kinase kinases 1 and 2 (CaMKK1 and CaMKK2) phosphorylate and enhance the catalytic activity of downstream kinases CaMKI, CaMKIV, and protein kinase B. Accordingly, CaMKK1 and CaMKK2 regulate key physiological and pathological processes, such as tumorigenesis, neuronal morphogenesis, synaptic plasticity, transcription factor activation, and cellular energy homeostasis, and promote cell survival. Both CaMKKs are partly inhibited by phosphorylation, which in turn triggers adaptor and scaffolding protein 14-3-3 binding. However, 14-3-3 binding only significantly affects CaMKK1 function. CaMKK2 activity remains almost unchanged after complex formation for reasons still unclear. Here, we aim at structurally characterizing CaMKK1:14-3-3 and CaMKK2:14-3-3 complexes by SAXS, H/D exchange coupled to MS, and fluorescence spectroscopy. The results revealed that complex formation suppresses the interaction of both phosphorylated CaMKKs with Ca2+ /CaM and affects the structure of their kinase domains and autoinhibitory segments. But these effects are much stronger on CaMKK1 than on CaMKK2 because the CaMKK1:14-3-3γ complex has a more compact and rigid structure in which the active site of the kinase domain directly interacts with the last two C-terminal helices of the 14-3-3γ protein, thereby inhibiting CaMKK1. In contrast, the CaMKK2:14-3-3 complex has a looser and more flexible structure, so 14-3-3 binding only negligibly affects the catalytic activity of CaMKK2. Therefore, Ca2+ /CaM binding suppression and the interaction of the kinase active site of CaMKK1 with the last two C-terminal helices of 14-3-3γ protein provide the structural basis for 14-3-3-mediated CaMKK1 inhibition.
Keywords: Calcium-Calmodulin-Dependent Protein Kinase Kinase; fluorescence spectroscopy; SAXS; hydrogen/deuterium exchange coupled to MS; difrakce rentgenového záření; protein-protein interaction; fosforylace; Scattering, Small Angle; Phosphorylation; 14-3-3 proteins; kinasa proteinkinasy závislé na vápníku a kalmodulinu; calcium/calmodulin-dependent protein kinase; X-Ray Diffraction; proteiny 14-3-3; Catalytic Domain; CaMKK; maloúhlový rozptyl; 14-3-3 Proteins; katalytická doména